The Concept of Competition in Economic Theory - Klimašauskienė, Danguolė (Ekonomika, 2007)
The article addresses two problems surrounding the interpretation and implementation of competition policy - what is competition and how competition policy must be designed to protect competition in order to ensure its benefits to society. The concept of competition is central to economic theory, but its scope and meaning as well as the ways in which competition is perceived to work and contribute to economic development have been the subject of vigorous debate among theorists, policymakers, bureaucrats and business people. Indeed, the history of economic thought provides some deeply contrasting views about the meaning of competition. Amongst them, the concept of perfect competition has survived as the standard model for analysis and has had a profound influence on policymaking concerned with the regulation of competition. However, the notion of this form of competition is very different from the concept envisaged by classical economists such as Adam Smith. He and other classical economists regarded competition as a description of competitive behaviour, especially with respect to prices. Viewed in this way, competition acts as a force that would, in the long run, eliminate excessive profits and unsatisfied demand. Participants in the market would change price in response to market conditions principally through the process of rivalry. The contemporary Austrian school of thought and the economists influenced by it have been redefining the concept along classical lines, although with a much greater emphasis on invention, innovation, and technological process. Whereas classical economists thought competition to be primarily a behavioral term, the subsequent course of events turned it into a description of a particular market structure. Beginning from the 1920s, mathematical economists developed the so-called perfect competition model which it replaced the older theory. To economists, competition no longer meant rivalry and enterprise. Instead, it meant the equation of price and marginal cost. Most important, it meant that there must be many firms in non-concentrated industries. Once economists began to define competition in terms of market structure, they became more and more enamored with antitrust regulation as a way of forcing the business world to conform to their admittedly unrealistic theory of competition. The two definitions of competition have drastically different implications about the welfare consequences of monopoly and perfect competition. The notions of competition as a market structure and competition as a dynamic process are not only descriptive but normative as well. That is, they do not merely describe the nature of competition; they inform us that competition is socially beneficial, although in different ways. Competitive markets are socially preferable to other kinds of markets in terms of allocative and productive efficiency. On the other hand, neo-Austrians believe that their kind of competition is also socially desirable, because it promotes efficiency and social welfare. Since competition is a process, it can lead to a variety of market structures that can give efficient outcomes. It will only generate a competitive or atomistic market structure where market conditions and production process favour the operation of very small, efficient firms. Alternatively, production efficiency may have a scale dimension and require large firms, so that the highly concentrated industry can also be associated with efficiency. Successful innovations produce a greater social surplus, even if they result in the displacement of competitive markets by monopolistic markets. Tradeoff between static and dynamic welfare considerations is implicit in the competing notions of competition. The possibility of socially beneficial monopolistic markets carries significant implications for government policy. If one views competition largely as a structure, the government should be duly concerned about and attempt to influence the market structure. If one views competition largely as a dynamic process, the case for government interest in and interference with market structures is much weaker. More generally, a sound antitrust policy will have to take into account both static and dynamic considerations.